ISLAMIC EDUCATION LEARNING STRATEGY FOR STUDENTS WITH SPECIAL NEEDS IN THE NEW NORMAL ERA (CASE STUDY: SLB 'AISYIYAH TEMBUNG) - Mavianti Mavianti (Proceeding International Seminar of Islamic Studies, 2021)
This article aims to reveal Islamic religious education learning strategies for students with special needs in the new normal era (case study: SLB 'Aisyiyah, Tembung). The strategy carried out in this special school includes coordination with various parties such as the principal, teachers and parents of students so that the learning process can take place well. In addition, the readiness of schools to provide medical devices that can support the implementation of health protocols is also an important factor. However, even though the health protocol was declared ready, children with special needs still had a greater risk of exposure than children of their peers. This is of course related to the immune system of children with certain special needs being more vulnerable. The strategy pursued is of course to provide appropriate services for children with special needs in the new normal era. Mainly mental health for all parties involved in learning Islamic religious education for children with special needs needs to be prepared. And also it cannot be separated from the policies established by the authorities that can support the learning development of children with special needs in the new normal era. Keyword: PAI Learning, Special Needs, New Normal Era